Readiness of Students, Lecturers, and Stakeholders Towards TOEFL as a Graduation Policy: A Study at FTK UIN Mataram’s ELT Program - Ika Rama Suhandra; Yek Amin Azis (Universitas Islam Negeri Mataram, Indonesia, 2024)
ABSTRACT This study examines stakeholder readiness toward the implementation of TOEFL as a graduation requirement in the English Language Teaching (ELT) Study Program at the Faculty of Education and Teacher Training, UIN Mataram. The research employed a mixed-method design, integrating qualitative and quantitative approaches to obtain a comprehensive understanding of the issue. Data were collected through a TOEFL prediction test, open-ended questionnaires, and semi-structured interviews involving 400 students, 10 lecturers, and 3 administrators. Quantitative data from TOEFL scores were analyzed descriptively, while qualitative data from questionnaires and interviews were examined thematically. The findings indicate strong overall support for the policy across stakeholder groups. However, the average TOEFL score of 381 reveals a considerable gap between expected and actual English proficiency levels. Key challenges include limited curriculum integration, test anxiety, and insufficient preparation resources. Stakeholders emphasized the need for systematic curriculum embedding, regular practice tests, and strengthened institutional support. The study underscores the importance of context-sensitive and evidence-based interventions to bridge the gap between policy expectations and stakeholder readiness, contributing to more effective and equitable English proficiency policies in Indonesian teacher education. ABSTRAK Penelitian ini mengkaji kesiapan pemangku kepentingan terhadap penerapan TOEFL sebagai syarat kelulusan di Program Studi Pendidikan Bahasa Inggris (PBI) Fakultas Tarbiyah dan Keguruan UIN Mataram. Penelitian ini menggunakan desain mixed-method yang mengintegrasikan pendekatan kualitatif dan kuantitatif untuk memperoleh pemahaman yang lebih komprehensif. Data dikumpulkan melalui tes prediksi TOEFL, kuesioner terbuka, dan wawancara semi terstruktur kepada 400 mahasiswa, 10 dosen, dan 3 tenaga kependidikan. Data kuantitatif dari skor TOEFL dianalisis secara deskriptif, sedangkan data kualitatif dianalisis melalui pendekatan tematik. Hasil penelitian menunjukkan adanya dukungan yang kuat terhadap kebijakan tersebut dari seluruh pemangku kepentingan. Namun, skor TOEFL rata-rata sebesar 381 mengindikasikan adanya kesenjangan yang cukup besar antara capaian aktual dan standar yang diharapkan. Hambatan utama meliputi keterbatasan integrasi kurikulum, kecemasan menghadapi tes, serta kurangnya sumber daya untuk persiapan. Para pemangku kepentingan merekomendasikan pengintegrasian TOEFL secara sistematis ke dalam kurikulum, pelaksanaan tes praktik secara rutin, serta penguatan dukungan kelembagaan. Penelitian ini menekankan pentingnya intervensi berbasis konteks dan data untuk menjembatani kesenjangan antara tuntutan kebijakan dan kesiapan aktual, sehingga dapat mendukung kebijakan kecakapan bahasa Inggris yang lebih efektif dan berkeadilan dalam pendidikan guru di Indonesia.